The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1103/physrevb.78.214414
|View full text |Cite
|
Sign up to set email alerts
|

Phase diagram and entanglement of the Ising model with Dzyaloshinskii-Moriya interaction

Abstract: We have studied the phase diagram and entanglement of the one dimensional Ising model with Dzyaloshinskii-Moriya (DM) interaction. We have applied the quantum renormalization group (QRG) approach to get the stable fixed points, critical point and the scaling of coupling constants. This model has two phases, antiferromagnetic and saturated chiral ones. We have shown that the staggered magnetization is the order parameter of the system and DM interaction produces the chiral order in both phases. We have also imp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
104
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(105 citation statements)
references
References 40 publications
1
104
0
Order By: Relevance
“…The pairwise entanglement of the system is also discussed by means of quantum renormalization group (QRG) method [16,17]. Very recently, the spin−1/2 Ising and Heisenberg models are studied by using the same method by a group of Iran and found that the systems exist QPT [18][19][20][21]. It is also shown that the nonanalytic behavior of the entanglement and the scaling behaviors closing to the quantum critical point are obtained.…”
Section: Introductionmentioning
confidence: 99%
“…The pairwise entanglement of the system is also discussed by means of quantum renormalization group (QRG) method [16,17]. Very recently, the spin−1/2 Ising and Heisenberg models are studied by using the same method by a group of Iran and found that the systems exist QPT [18][19][20][21]. It is also shown that the nonanalytic behavior of the entanglement and the scaling behaviors closing to the quantum critical point are obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Although the presence of bond alternation breaks the translation invariance of the Hamiltonian it does not change the symmetry of the ground state which has already been spontaneously broken due to antiferromagnetic long range order. A comparison of our results with 13 concludes that the bond alternation does not change the universality class of the model as far as λ = 1.…”
Section: Summary and Discussionmentioning
confidence: 92%
“…In the absence of the LF, the ground state phase diagram of the model is known [27][28][29] . The spectrum of the model for −D < J ≤ D is gapless and the system is in the so-called Luttinger-liquid (LL) phase with a power-law decay of correlations.…”
Section: The Modelmentioning
confidence: 99%